Incidental neuroimaging findings in South African adult research participants with and without neuropsychiatric disorders - Chanellé Hendrikse; Tina Malan; Stéfan du Plessis; Jonathan Carr; Martin Kidd; Robin Emsley; Soraya Seedat (NeuroImage: Reports)
There is a lack of comparative data on the occurrence and clinical significance of incidental neuroimaging findings (IFs) in adult research participants with neuropsychiatric disorders and healthy controls. We investigated and compared the frequency, clinical significance and predictors of IFs on structural brain magnetic resonance imaging (MRI) scans of research participants between the ages of 18–78 years living in Cape Town, South Africa. Our sample (N = 295) included individuals with posttraumatic stress disorder (n = 122) or Parkinson's disease (n = 21), and healthy controls (n = 152). T1 ME-MPRAGE weighted structural MRI scans were acquired and subsequently reviewed for IFs by radiologists. A neurologist reviewed radiological reports and categorised IFs according to their estimated clinical significance. IFs were observed on the scans of 95 (32%) participants but most IFs were either judged to be clinically non-significant (49%) or of unknown clinical significance (32%). Eighteen participants (6%) had clinically significant findings that required referral for further clinical management. Age was a significant predictor of having an IF, whereas a diagnosis of Parkinson's disease was a significant predictor of having a clinically significant IF.